Evolution of selective COX-2 inhibitor from Alangium salvifolium: an in silico approach - Raju Dash, Md. Tanveer Ahsan, S. M. Zahid Hosen, Md. Golamur Rahman, Talha Bin Emran , Mir Muhammad Nasir Uddin (Journal of Applied Pharmaceutical Science, 2015)
Pain and inflammation are linked with a number of pathological conditions. Several studies are in progress worldwide to find natural healing agents with better safety profile. Our current study was aimed to evaluate Alangium salvifolium (family: Alangeaceae) derived analgesic compounds for therapeutic drug discovery by computational approach. Literature based studies were used to explore the compounds of A. salvifolium. Ligands were prepared by following the appropriate procedures and finally in silico molecular docking analysis performed by GOLD 4.2. After post docking analysis, salviifosides A of Alangium salvifolium was found to have interaction on COX-2 protein by obtaining highest fitness score 50.64 and molecular interaction suggests that it could be a potent anti-inflammatory compound and it may be worth for further clinical trials.
Keywords: Alangium salvifolium, Analgesic, Anti-inflammatory, COX-2, Salviifosides A, GOLD.